2019
DOI: 10.1021/acs.jnatprod.8b01025
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay-Guided Isolation of Fungistatic Compounds from Mimosa caesalpiniifolia Leaves

Abstract: A bioassay-guided phytochemical study of a Mimosa caesalpiniifolia leaf extract with antifungal activity permitted the identification of 28 compounds, including the new 6-(β-boivinopyranosyl)apigenin (1), 8-(β-oliopyranosyl)apigenin (2), (E)-6-(2-carboxyethenyl)apigenin (3), (E)-8-(2carboxyethenyl)apigenin (4), and 7,5″-anhydro-6-(α-2,6dideoxy-5-hydroxyarabinohexopyranosyl)apigenin (5). The structures of the new compounds were determined by comprehensive spectroscopic analysis, including 1D and 2D NMR techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 45 publications
(96 reference statements)
1
13
0
Order By: Relevance
“…Genistein acts primarily as an antioxidant phytoestrogen without observable fungicide properties [ 25 ]. Similarly, ethyl gallate shows little antifungal effect, but its synergistic activity is detectable [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genistein acts primarily as an antioxidant phytoestrogen without observable fungicide properties [ 25 ]. Similarly, ethyl gallate shows little antifungal effect, but its synergistic activity is detectable [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…8,39 Phytochemical analysis of EEM showed the presence of flavonoids, saponins, alkaloids, terpenoids and tannin, which have been reported to be present in other plants with anti-inflammatory properties. 22,40 It is possible that the bioactive compounds present in the hydroalcoholic extract of the leaves of M. caesalpiniifolia are responsible for the anti-inflammatory and antioxidant effects described for the extract. Particularly flavonoids, which have the ability to capture free radicals, can overcome the effects of known antioxidants, such as, for example, vitamins A and E.…”
Section: Discussionmentioning
confidence: 99%
“…Phytochemical analysis in some Mimosa species showed the presence of flavonoids, saponins, alkaloids, terpenoids, non-protein amino acids (mimosa), tannins and fatty acids. 20 Silva et al, 21 identified two important flavonoids from the leaves of M. caesalpiniifolia, catechin, 2,3 dihydroquercetagetine and procyanidin B2 [(epi) catechin-(epi) catechin] and the authors Silva et al, 22 Due to the use of M. caesalpiniifolia leaves in folk medicine to combat inflammatory diseases, without scientific evidence of this potential therapeutic application, the aim of the study was to evaluate the properties of hydroalcoholic extract of M. caesalpiniifolia (EEM) leaves responsible for is anti-inflammtory and antioxidant effects, which help EEM in the ethnopharmacological use in popular medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Plants accounted for nearly ten antifungal leads within the last decade ( Figures 11 and 12, 56-64). The flavonoid (E)-6-(2-carboxyethenyl) apigenin (56) was isolated from an extract of Mimosa caesalpiniifolia Benth., a Brazilian medicinal plant commonly known as "sabiá" or "sansão-do-campo" [45]. The compound inhibits C. krusei with an IC50 of 44 nM, although it was inactive against C. glabrata.…”
Section: Natural Product Antifungal Leads From Plantsmentioning
confidence: 99%